Analysis of Corrosion-Induced Diffusion Layer in ZK60A Magnesium Alloy. Issue 13 (5th October 2016) - Li, Shumin; Chen, Ziguang; Wang, Fei; Cui, Bai; Tan, Li; Bobaru, Florin
Abstract : Corrosion-induced damage in ZK60A magnesium alloy is analyzed via chemo-mechanical tests. A certain "diffusion" corrosion layer (DCL) is identified, where partial corrosion takes place. This layer is different from the corrosion product layer (CPL). Nanoindentation analysis shows that corrosion modifies mechanical properties in the DCL, which extends up to 8–9 micrometers into the bulk, away from the CPL. Measurements over the DCL indicate a lower elastic modulus and lower fracture toughness compared with the bulk, as well as higher variance (heterogeneity). Elemental analysis confirms the layer is composed of partially-oxidized magnesium and diffused chloride ions. Gradual changes in mechanical properties of the DCL, and the fact that it is not easily separable from the bulk, increase the likelihood that cracks may initiate easier here and could propagate into the bulk under external stresses.